Targeting DNA Damage Repair for Immune Checkpoint Inhibition: Mechanisms and Potential Clinical Applications - Sun, Wei; Zhang, Qing; Wang, Runkun; Li, Yang; Sun, Yue; Yang, Lin (Frontiers in Oncology, 2021)
DNA damage repair (DDR) pathways play an essential role in maintaining genomic integrity. DDR dysfunction leads to accumulated DNA damage, predisposition to cancer, and high sensitivity to chemotherapy and radiotherapy. Recent studies have demonstrated that DDR status is associated with response to immune checkpoint blockade (ICB). Among the DDR pathways, mismatch repair is the most recognized predictive biomarker for ICB. Furthermore, preclinical and early clinical studies suggest the rationale of combining agents targeting the DDR pathways with immune checkpoint inhibitors (ICIs). In the present review, we describe the predictive role of DDR pathways in ICIs and summarize the advances in potential combination strategies of novel agents targeting DDR with ICIs for cancer treatment.